2002
DOI: 10.1111/j.1745-3984.2002.tb01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Grades and Test Scores: Accounting for Observed Differences

Abstract: Why do grades and test scores often differ? A framework of possible differences is proposed in this article. An approximation of the framework was tested with data on 8,454 high school seniors from the National Education Longitudinal Study. Individual and group differences in grade versus test performance were substantially reduced by focusing the two measures on similar academic subjects, correcting for grading variations and unreliability, and adding teacher ratings and other information about students. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
3
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(218 citation statements)
references
References 69 publications
11
173
3
6
Order By: Relevance
“…In contrast, IQ predicted changes in standardized achievement test scores over time better than did self-control. h ese i ndings are consistent with those of Willingham, Pollack, and Lewis ( 2002 ), who examined data from 8,454 high school seniors in the National Education Longitudinal Study (NELS). Selfregulated behaviors such as attending class regularly and promptly, participating in class activities, completing work on time, and avoiding drug and gang activity were more strongly associated with grade point average (GPA) than with standardized achievement test scores.…”
Section: Where Course Grades and Standardized Achievement Test Scoressupporting
confidence: 75%
See 1 more Smart Citation
“…In contrast, IQ predicted changes in standardized achievement test scores over time better than did self-control. h ese i ndings are consistent with those of Willingham, Pollack, and Lewis ( 2002 ), who examined data from 8,454 high school seniors in the National Education Longitudinal Study (NELS). Selfregulated behaviors such as attending class regularly and promptly, participating in class activities, completing work on time, and avoiding drug and gang activity were more strongly associated with grade point average (GPA) than with standardized achievement test scores.…”
Section: Where Course Grades and Standardized Achievement Test Scoressupporting
confidence: 75%
“…Why does self-regulation predict course grades better than standardized achievement test scores? Course grades and standardized test scores are generally highly correlated (Willingham et al, 2002 ). Not surprisingly, therefore, standardized achievement tests and grades are ot en wrongly assumed to be "mutual surrogates; that is, measuring much the same thing, even in the face of obvious dif erences" (Willingham et al, 2002 , p. 2).…”
Section: Where Course Grades and Standardized Achievement Test Scoresmentioning
confidence: 99%
“…Although none of these correlations was statistically significant (p> 0.05) the result showed that negative lecturer relationships were rather related with high academic performance of students. This was not in line with other findings, most of which were focused at the beginning to middle level of education, that suggested that good or positive student-teacher relationship promotes high academic achievement while a negative relationship related to a downward trend in academic achievement (Ewnetu & Fisseha, 2008;Pianta, 1999;Willingham et al, 2002, Grobe & Bishop, 2001Haycock, 1998;Hughes & Kwok, 2007). This means that even-though positive relationship promotes academic performance, this might not be the case always especially at the higher educational level where socio-cultural practices, existing educational policies and mode of lecturing especially within the context and content of Ghanaian university education might have had tremendous impact on how students perceived and relate with lecturers in order to enhance their academic performance.…”
Section: Journal Of Social Science Studiescontrasting
confidence: 42%
“…This was further strengthen in Hughes and Kwok (2007), who found out that students demonstrated higher achievement when there was a higher level of supportive relationships with teachers. This means that in a learning environment where students have good relationship with their teachers, students are more likely to earn higher grades (Willingham et al, 2002, Grobe & Bishop, 2001. Likewise, Haycock (1998) revealed that the difference between good and bad instructor relationship behaviour is measured in terms of learning achievement to a great deal.…”
Section: Review Of Related Literaturesmentioning
confidence: 99%
“…Over the years, Willingham maintained an interest in investigating the differences between grades and test scores, especially with respect to differential predictive validity (Willingham et al 2002). Related contributions include Lewis and Willingham (1995) and Haberman (2006).…”
Section: Predictionmentioning
confidence: 99%